Pyrrole alkaloids and ergosterols from Grifola frondosa exert anti-α-glucosidase and anti-proliferative activities. (April 2018) - Chen, Shaodan; Yong, Tianqiao; Xiao, Chun; Su, Jiyan; Zhang, Yifan; Jiao, Chunwei; Xie, Yizhen
Highlights: Bioactive anti-α-glucosidase and anti-proliferative fraction of Grifola frondosa were determined. 20 compounds, including one new compound were isolated from the bioactive fraction GF-3. Pyrrole alkaloids were found in G. frondosa for the first time. Pyrrole alkaloids showed potent inhibition against α-glucosidase, ergosterols displayed inhibition against tumor cells. G. frondosa may be beneficial to diabetic or tumor patients. Abstract: Previously, polysaccharides with hypoglycemic effects from G. frondosa were reported by us. To explore compounds against α-glucosidase and human tumor cells, three extractive fractions (GF-1–GF-3) were prepared from G. frondosa ethanol extraction (GF) by chromatographic column. Rather than GF-1 and GF-2, the fraction GF-3 demonstrated inhibitory actions against α-glucosidase and proliferation of human tumor cells dominantly. To identify the bioactive compounds in GF-3, one new compound named pyrrolefronine together with 19 known ones, which included seven pyrrole alkaloids, nine ergosterols and three others, were isolated and characterized from GF-3. Significantly, pyrrole alkaloids were found in G. frondosa for the first time, showing potent inhibition against α-glucosidase. Obtained ergosterols displayed inhibition against proliferation of tumor cells. This study provides a basis for further development and utilization of G. frondosa as natural nutraceuticals and functional food ingredients.